2012
DOI: 10.1021/es204556c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Sulfuric Acid Contribution to New Particle Growth

Abstract: The Nano Aerosol Mass Spectrometer (NAMS) was deployed to rural/coastal and urban sites to measure the composition of 20-25 nm diameter nanoparticles during new particle formation (NPF). NAMS provides a quantitative measure of the elemental composition of individual, size-selected nanoparticles. In both environments, particles analyzed during NPF were found to be enhanced in elements associated with inorganic species (nitrogen, sulfur) relative to that associated with organic species (carbon). A molecular appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 77 publications
4
82
0
Order By: Relevance
“…During NPF, the sulfur and nitrogen mole fractions are larger and the carbon mole fraction is smaller than immediately before or after each event. A similar dependence of elemental mole fraction was noted previously for NPF in other locations (Bzdek et al, 2011(Bzdek et al, , 2012b. Note, however, that whereas the relative concentrations of S and C are anti-correlated, the absolute amounts of particulate S and C both increase substantially during NPF because there is a substantial increase in nanoparticle mass.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…During NPF, the sulfur and nitrogen mole fractions are larger and the carbon mole fraction is smaller than immediately before or after each event. A similar dependence of elemental mole fraction was noted previously for NPF in other locations (Bzdek et al, 2011(Bzdek et al, , 2012b. Note, however, that whereas the relative concentrations of S and C are anti-correlated, the absolute amounts of particulate S and C both increase substantially during NPF because there is a substantial increase in nanoparticle mass.…”
Section: Resultssupporting
confidence: 81%
“…It is reasonable to assume all of the sulfur in these particles exists in the form of sulfate (Bzdek et al, 2012b). First, off-line and on-line molecular composition analyses of collected ultrafine particles in this location show sulfate as a major constituent in nanoparticles, with little to no contribution from other sulfur-containing species (Smith et al, 2010).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Bzdek et al (2012) reports that NO 3 -, NH 4 + and organics contribute to 54-59% of new particle growth, whereas sulphates are responsible for the remaining 41-46% of the observed growth. Smith et al (2008) showed that the major compound of the newly formed particles are organics (~84%) and include organic acids (formate, acetate), hydroxyl organic acids and nitrogen-containing organic compounds.…”
Section: Meteorological Conditions Favouring Particle Shrinkagementioning
confidence: 99%